The Comparative Analysis of Bond Strength on Lightweight Concrete Block Surfaces Using Special Adhesive and Conventional Mortar - Argya Damuri; Andi Marini Andriani; Gunaedy Utomo (Civil Engineering Dept, Balikpapan State Polytechnics, 2026)
Indonesia, as an earthquake – prone country, requires wall materials that are strong, efficient, and resistant to cracking. Lightweight concrete blocks have become one of the modern construction alternatives due to their light weight, high dimensional precision, and good thermal and sound insulation properties. However, the bonding quality between blocks remains a determining factor for wall durability under loads and vibrations. This strudy aims to analyze the effect of mixture composition on bond strength and to compare the use of specialized adhesive with conventional mortar. Samples of lightweight concrete blocks were produced using Portland cement type I, local fine aggregates from Muara Samu, water, and foam agent with variations of 2%, 4%, and 6%. The foam agent was incorporated using 4 bar air pressure, and specimens were cured for 28 days according to SNI standards. The test result show that specialized adhesive provides higher bond strength compared to conventional mortar. Bond strength decreases with increasing foam agent content, with average values for specialized adhesive of 0.80 MPa (2%), 0.73 MPa (4%), and 0.69 MPa (6%), while conventional mortar yielded 0.55 MPa (2%), 0.43 MPa (4%), and 0.39 MPa (6%). The largest difference occurred at 6% foam agent, amounting to 42.96%. These findings confirm that the use of local fine aggregates produces lightweight blocks with good bonding quality, while supporting sustainable development through regional resource optimization.